Can customized implants correct enophthalmos and delayed diplopia in post-traumatic orbital deformities? A volumetric analysis. Issue 9 (September 2016) - Pedemonte, C.; Sáez, F.; Vargas, I.; González, L.E.; Canales, M.; Salazar, K.
Abstract: The purpose of this study was to determine whether orbital reconstruction with customized implants can correct post-traumatic orbital deformities such as late enophthalmos and delayed diplopia. The hypothesis proposed was that an overcorrection of the orbital volume is needed to resolve enophthalmos. A retrospective observational descriptive study was conducted. Patients with a major trauma who required customized orbital implants for the delayed treatment of unilateral orbital fractures that had initially been operated on using titanium mesh and/or osteosynthesis plates were included. The orbital volumes of the unaffected contralateral side, of the affected orbit after initial reconstruction with mesh, and of the affected orbit subsequently reconstructed with the customized implant were calculated. All of the patients included in this study had diplopia in the gaze position prior to the installation of the implant. In addition, they all had severe enophthalmos. After surgery, no patient with a customized implant showed diplopia. The enophthalmos was corrected in all but one case. On average, orbits reconstructed with customized implants had lower volumes compared to the unaffected contralateral side. In cases where the enophthalmos was resolved, the volume was reduced by an average of 8.55%. Further studies using a larger number of cases and with controlled volumetric corrections using CAD/CAM are needed.